THE EFFECT OF GDP ON PROFITABILITY LEVEL OF RETURN ON EQUITY IN MANDIRI SHARIA BANKS IN INDONESIA 2010-2019 PERIOD - Farid Ardyansyah (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2021)
Sharia banks are banks that are in their operational system or management based on sharia principles. Financial ratios that maximize added value for capital owners become the main framework in assessing the performance of a Sharia bank. An indicator to measure the bank's financial performance is to look at the level of profitability. Gross Domestic Product, is a macroeconomic variable for the economic growth of a country. The type of research in this research conducted by researchers is quantitative research. In this study, researchers conducted a study on the Effect of Gross Domestic Product (GDP) on Profitability Return On Equity (ROE) In Sharia Banks in Indonesia Period 2010-2019. The results of this study show that GDP variables have a Sig value. 0.002< 0.05 (Sig. value is less than probability) so that the VARIABLE GDP (X) has a significant effect on the variable ROE (Y). while the calculated t value is -9,808 > 2,024 (t count is greater than the table t and remains in the negatively influential area).